Estudio de las variaciones de carbohidratos lípidos, proteínas y valor energético en el alimento natural y artificial en estanques de cultivo de camarón - Sandoval Coyago, Cristhian (2005)
The present work was done at Mariluna shrimp ponds premises, Guarumal – Santa Rosa – El Oro. Biochemical analyses were carried out in the Mariluna shrimp ponds laboratory for water quality testing, and in the Bromatology Laboratory of the Chemical Sciences College of the University of Machala.